The chemical composition and antioxidant activities of basil from Thailand using retention indices and comprehensive two-dimensional gas chromatography - Pripdeevech P. (2014)
The chemical compositions of essential oils obtained from Ocimum basilicum var. thyrsiflora (1.39 % dry weight) and Ocimum basilicum (0.61 %) were analyzed by GC-MS. Seventy-three constituents representing 99.64 % of the chromatographic peak area were obtained in the O. basilicum var. thyrsiflora oil, whereas 80 constituents representing 91.11 % observed in the essential oil of O. basilicum were obtained. Methyl chavicol (81.82 %), β-(E)-ocimene (2.93 %) and α-(E)-bergamotene (2.45 %) were found to be the dominant constituents in O. basilicum var. thyrsiflora oil while O. basilicum contained predominantly linalool (43.78 %), eugenol (13.66 %) and 1,8-cineole (10.18 %). The clear separation of the volatiles in all samples, demonstrated by the application of GC×GC, resulted in significantly different fingerprints for the two types of basil. The O. basilicum oil showed strong antioxidant activity while the oil of O. basilicum var. thyrsiflora exhibited very low activity, which was attributed to the significant differences in linalool and eugenol contents in these essential oils. 2010 Copyright (CC) SCS.